Tuned Mass Dampers for Response Reduction of a Reinforced Concrete Chimney Under Near-Fault Pulse-Like Ground Motions - Elias, Said; Rupakhety, Rajesh; Ólafsson, Simon (Frontiers in Built Environment, 2020)
The article investigates response mitigation of a reinforced concrete (RC) chimney subjected to pulse-like near-fault ground motions using tuned mass damper (TMD) schemes. The total height of the chimney is 250 m with a mass of 11109 ton. Three TMD schemes are used: single tuned mass damper (STMD), multiple TMDs having equal stiffness (w-MTMDs) and multiple TMDs having equal masses (e-MTMDs). The STMD is tuned to the fundamental frequency of the chimney while both w-MTMDs and e-MTMDs have three TMDs for controlling each of the first and second modes (total of 6 TMDs) of vibration. Response of the uncontrolled and controlled structures is calculated for 69 recorded ground motions containing a dominant velocity pulse. Displacement and acceleration at top node of the RC chimney are the response of interest for performance assessment. It is found that e-MTMDs are more effective and robust than other schemes. It is also found that the pulse period of ground motion plays a very important role in how effective the control schemes are. There is a large variability in the reduction of response across these ground motions, and optimization methods independent of ground motion are not robust. There is a need for more advanced optimization methods incorporating information about local seismic sources.